DIAGNOSIS DAN ANALISIS KETELITIAN GERAK MEJA MACHINING CENTER OKUMA & HOWA MILLAC - 4H - Darto
The high price of machine tools must be equalized with maximal performance, and it needs to be proved with several performance tests. The test is not only need to be carried out once as the acceptance test but also need to be carried out periodically, in order to keep the machine on it 's best performance. In this research, machine tools will be tested especially on its accuracy of x-axis direction table movement with laser interferometer. Accuracy of table movement test content with positioning accuracy test, angular movement accuracy test and straightness movement accuracy test.- Error in machining center table movement was not an individual error, but it was a result of several errors, such as imperfect component, incorrect assembly of machine tools and error in measuring system. In order to perform effective and efficient diagnoses, homogenous transformation matrix are used to build the model of table movement error. The model of table movement error are built by applying the concept of five bearing contacts on slide ways along with the concept of misalignment between lead screw and guide ways. Trough this model, the form of wear of both guide ways and ballscrew can be determined by comparing the graphic resulted from modeling with the graphic came from direct measuring with laser interferometer. This research gives the conclusions that the direct measuring for error in straightness movement is close to the model. But on the other side, direct measuring on angular movement error of table still has significant difference from the model.